Operationalizing computerized testing in mathematics competition - Shanmugam, S. Kanageswari Suppiah; Kor, Liew-Kee; Chinnappan, Mohan (IGI Global - All Rights Reserved, 2019)
This chapter seeks to take a modest and yet formative approach in proposing computer-based test (CBT) as the inevitable next wave in digital assessment. The major section reports on the practical design of developing and administering CBT in a mathematics competition by HOTS educational innovation development (HEID) in a mathematics competition. This chapter describes the CBT developmental process undertaken by HEID, which focuses on constructing multiple-choice test items, administering CBT, and scoring the test. While CBT offers the possibility of improving assessment, the process of preparing items and conducting online competition have nevertheless encountered several challenges such as getting quality test items, school and teacher readiness, seat time in front of computer, computer compatibility, and internet speed. As with many other educational reforms at infancy, more research in the area of implementing CBT to facilitate international competitions is needed in landscaping the assessment platform of Education 4.0.